Enzymatic potential and biosurfactant production by endophytic fungi from mangrove forest in Southeastern Brazil - Vivian Martinho (AMB Express, 2019)
Abstract Microbial activity is the main route for cycling mangrove nutrients. In general, microorganisms have abilities to degrade lignocellulosic compounds. Among the biotechnological potential of the microbiota from mangroves, it is noteworthy about endophytic fungi, which can be considered as effective sources of different bioactive compounds. In this sense, thirty (30) endophytic fungi were isolated from mangrove forest sampling Cananeia, SP, Brazil. These microorganisms were analyzed about their enzymatic activities including: lignin peroxidase EC 1.11.1.14, manganese peroxidase EC 1.11.1.13 and laccase EC 1.10.3.2, as well endo-cellulase EC 3.2.1.4 and endo-xylanase EC 3.2.1.8. Besides that, production of bioactive secondary metabolites like biosurfactant and/or bioemulsifier was also investigated. As results, nineteen (19) isolates were selected about their ligninolytic abilities, nine (9) of them about cellulase activity and thirteen (13) showed xylanase abilities. The fungal isolate named as 3(3), characterized as Fusarium sambucinum, showed a prominent lignin peroxidase (42.4 U L−1) and manganese peroxidase (23.6 U L−1) activities. The isolate 63.1, also related to Fusarium sp. genera, was selected about its laccase activity (41.5 U L−1). From all the investigated fungi, the isolate 47(4) Trichoderma camerunense was selected about its cellulolytic and xylanolytic activities, showing 45.23 and 26.09 U mL−1, respectively. The same fungi also showed biosurfactant ability demonstrated by superficial tension decreasing to 38 mN/m. In addition, fifteen (15) fungi exhibited bioemulsifier activity, with E24 values up to 62.8%.